(untitled) (Journal of Oriental Studies, 2020)
This article seeks to explore the meaning, origins, and the content of the concept of “community of common destiny” that has become central to current foreign policy of China. On the basis of the works developed mainly by the Chinese and Western scholars, the author argues that the concept of “community of common destiny” marks the start of the new era in China’s foreign policy led by the fifth generation of Chinese leadership. After providing a thorough discussion on the concept itself the article analyzes its implications on China’s foreign policy behavior in the near future. It posits that this concept entails a more proactive foreign policy, frequent Chinese involvement in global governance issues, efforts directed towards promoting China’s positive image abroad, active engagement in regional organizations and acting as a responsible power. The article concludes that the active promotion of this new concept at major international events by the Chinese leadership demonstrates China’s willingness to act according to its growing international clout. Key words: “community of common destiny”, global governance, proactive foreign policy, fifth generation.